Konsep AMO Dalam Penerapan Ghrm Mewujudkan Digitalisasi Kesehatan Di Lingkungan Smart City - M. Abdullah Syaefuddina; Asep Saifuddin; Winaya Purwanti (Cakrawala Akuntansi & Manajemen, 2022)
In the dynamic and growing society, the digitalization process has been a must thing to do in every aspects. Particularly in life necessities like health that is one of the essential parts in a Smart City ecosystem. The need to transform into Society 5.0 and the pandemic condition are factors that influence the needs for ‘multiple product in one touch service’ app that emphasizes on integrated Healthcare based on Green Human Resources Management (GHRM). The purpose of this research is to see the effect of GHRM concept’s effectivity has on the implementation of healthcare digitalized agregation at Indonesia from the viewpoint of AMO (Ability – Motivation – Opportunity) theory, from the health consultation, pharmacy serevices, to medication, as well as looking for applied effective and efficient digital-based solutions. The research method is mixed between primary and secondary data, both are qualitative-based. The result is to give a solution that the need for GHRM is a crucial matter for giving value to consumers. And so, it takes an integrated healthcare app named InDimensia Mobile App (Integrated Digital Medicine for Smart City) with features that are needed by society and also can be the answer to face the cllanges from Society 5.0 and Smart City. This healthcare app will be an effective and efficient solution for modern society in order to prepare themselves to face the transformation to Society 5.0.